Co-conversion of Industrial Biowaste Mixtures by Hydrothermal Method and Application to $Cu^{2+}$ Adsorption - Sayğılı, Gülbahar Akkaya; Sayğılı, Hasan (My University, 2023)
In present work, a novel carbonaceous product (HPSHC) was obtained by hydrothermal co-carbonization (co-HTC) of hazelnut and peanut shells (HS and PS). HS and PS were mixed at a mixing ratio of 1:1 by mass and subjected to co-HTC treatment at 220°C for 6 hours’ reaction time. The physicochemical characteristics of the produced HPSHC such as atomic carbon content, mass yield, higher heating value and energy density were determined. In addition, attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR) was taken to determine the surface functional groups and scanning electron microscopy (SEM) images were taken to highlight the surface morphology. HPSHC was utilize as a sorbent sample in copper ions (Cu(II)) adsorption. The rate and equilibrium parameters of the system were calculated by kinetic and isotherm modeling of the adsorption. Kinetic studies showed that the adsorption was consistent with the pseudo-second order kinetic model, and isotherm studies showed that it was obeyed the Langmuir model. A theoretical maximal uptake capacity $(q_m)$ was calculated 39.90 mg/g. In addition, as a result of thermodynamic calculations using equilibrium constants, it was observed that the adsorption of Cu(II) on HPSHC is a spontaneous and endothermic process.
Keywords: Cu(II); Isotherm; Kinetic; Co-hydrothermal carbonization; Hazelnut shell; Peanut shell